Using Reclaimed Water for Landscape Irrigation - Christopher J. Martinez; Mark W. Clark (EDIS)
AE449, a 6-page fact sheet by Christopher J. Martinez and Mark W. Clark, discusses how to manage for salinity and nutrients contained in reclaimed water when using it for landscape irrigation. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2009.